Enhanced CO2 capture using organic acid structure modified waste eggshell derived CaO sorbent. Issue 1 (February 2021) - Nawar, Azra; Ali, Majid; Khoja, Asif Hussain; Waqas, Adeel; Anwar, Mustafa; Mahmood, Mariam
Abstract: In this study, the waste eggshell has been utilised to synthesise structure modified CaO using organic acids and employed for CO2 capture in the thermogravimetric analysis (TGA) based systems. Different characterisation techniques were used such as XRD, SEM/EDS, XRF, N2 sorption-desorption (BET) and TGA to investigate the suitability for CO2 adsorption. The modified CaO using organic acids showed high surface area, easy upgradation of pore structure makes the CaO a suitable sorbent for CO2 capturing as an economical sorbent. Three of the organic acid modified sorbent achieved the highest conversion and stability over a period of 20 cycles. Citric acid modified sorbent (CaO CA-10%) obtained a CO2 uptake of 0.38 g CO2 /g sorbent (CaO conversion of 55%) that was highest among the acid used whereas in term of stability malic acid modified sorbent (CaO MA-10%) has the lowest average decay rate of 4.43 mg CO2 /cycle as compared to various acids used in this work. It is concluded that modified surface structure by employment of organic acids lead to the reduction of sintering and led towards better sorbents performance towards CO2 capturing for multiple cycles. Graphical Abstract: ga1 Highlights: Synthesis of acid treated surface modified eggshell based CaO sorbent. Surface modified sorbent shows high surface area and porous structure. Acid treated sorbents shows stable uptake of CO2 for 20 cycles. Citric acid modified sorbent obtained a CO2 uptake of 0.38 g CO2 /g sorbent.